PENGARUH PENGARUH KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL, DAN PERTUMBUHAN LABA TERHADAP TAX AVOIDANCE - Damaris Yolanda Sihombing; Ibram Pinondang Dalimunthe (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine independent commissioners, institutional ownership and profit growth on tax avoidance in Pharmaceuticals sub-industry companies listed on the IDX for the 2016-2020 period. This type of research is quantitative, the data used is secondary data in the form of financial reports obtained through the official website of the Indonesian Stock Exchange. The selected sample is 9 companies with purposive sampling method sample selection technique. The data analysis technique used is panel data regression analysis by selecting a regression model, model testing, classical assumption testing and hypothesis analysis using the eviews 10 program data processing. The results show that  partially independent commissioners effected tax avoidance, institutional ownership had an effected on tax avoidance while profit growth did not have effect on tax avoidance. It showed, the variables of independent commissioners, institutional ownership, and profit growth had an effect on tax avoidance